Semen antioxidant study in male patients at East Coast Malaysia - Abdul Wahab, Azantee Yazmie; Ramli, Roszaman; Abd Rahman, S.; Md Isa, Muhammad Lokman; Mohd Yatim, Hayati; Mohd Bustaman, Siti Khadijah; M Zulkifli, S N (2014)
Reactive oxygen species (ROS) is believed to be one of the factors that cause male infertility. Antioxidants in the seminal plasma plays important role in protecting sperm from ROS. The purpose of this study is to determine the antioxidants level in semen sample in male patients without antioxidant treatment at IIUM Fertility Centre, Malaysia. A total of 43 semen samples were taken and seminal fluid analysis (SFA) test was performed according to WHO 1999 guideline. Patients were 234 divided into two groups; normozoospermia and oligozoospermia. Semen samples were then stored in liquid nitrogen at 196 ?C using standard preservation technique. The samples were thawed and centrifuged to separate the seminal plasma and the sperm. The antioxidant levels of Vitamin C and Vitamin E in seminal plasma were measured using the spectrophotometer. Descriptive statistic was done for SFA to summarize the result of sperm parameters and antioxidant levels. It is shown in this study that the level of antioxidants, both Vitamin E and Vitamin C, are higher in the normozoospermia samples compared to the oligozoospermia samples (p<0.05). There is a positive correlation between the sperm concentration and the level of antioxidants.